Physiology of microalgae and their application to sustainable agriculture: A mini-review - Çakirsoy, Iffet; Miyamoto, Takuji; Ohtake, Norikuni (Frontiers in Plant Science, 2022)
Concern that depletion of fertilizer feedstocks, which are a finite mineral resource, threatens agricultural sustainability has driven the exploration of sustainable methods of soil fertilization. Given that microalgae, which are unicellular photosynthetic organisms, can take up nutrients efficiently from water systems, their application in a biological wastewater purification system followed by the use of their biomass as a fertilizer alternative has attracted attention. Such applications of microalgae would contribute to the accelerated recycling of nutrients from wastewater to farmland. Many previous reports have provided information on the physiological characteristics of microalgae that support their utility. In this review, we focus on recent achievements of studies on microalgal physiology and relevant applications and outline the prospects for the contribution of microalgae to the establishment of sustainable agricultural practices.